Alih Pengetahuan Komunikasi Lingkungan Berbasis Sanitasi dan Higienitas Produksi bagi Pelaku UMKM Pulau Panggang - Marta, Rustono Farady; Ulung, Alessandro Kurniawan; Siregar, Sri Rachmawati H.; Rifandi, Teguh; Agustinus, Ferdinand; Dewis, Meilia; Fadhilla, Deva Naufal; Adrianmovich, Mochammad Zlatan; Muthmainah, Syifa Salmah (Universitas Prof. Dr. Moestopo (Beragama), 2025)
UMKM based on marine products in Panggang Island, Kepulauan Seribu, play an essential role in the coastal economy, yet sanitation and hygiene aspects still need strengthening through environmentally oriented approaches to ensure product quality and business sustainability. This study aims to enhance the capacity of UMKM actors through an initial socialization of community-based partnership empowerment. The activities were conducted using a Participatory Action Research (PAR) approach with a hybrid format, combining face-to-face and online sessions, along with participatory observation and group discussions. The main materials focused on Good Manufacturing Practices, production space management, raw material handling, and local product communication strategies to build consumer trust. The results indicated an increase in collective awareness among UMKM actors regarding hygienic practices, the ability to identify production constraints, and readiness to engage in follow-up training and intensive mentoring. These findings highlight that multi-stakeholder collaboration involving academia, government, and the community can strengthen the UMKM ecosystem, support local economic sustainability, enhance product competitiveness, and reinforce environmental communication strategies.